O museu do imigrante italiano “Eduardo Marcuzzo”: história e identidade, Vale Vêneto/RS - Foletto, Célia Terezinha (2019)
Italian immigration was a far-reaching event in the social, economic and religious life of individuals from different regions of Italy who settled in the central region of the state of Rio Grande do Sul. In this sense, the cultural heritage built and inherited by several generations is full of meanings, some are still very present in the social memory of the residents of Vale Vêneto, district of the town São João do Polêsine, region belonging to The Fourth Colony. In that place, there is the Italian Immigrant Museum Eduardo Marcuzzo (MIEM), founded on July 26, 1975, which has the most important collection of all time, with more than ten thousand artifacts, donated by community and refering to the daily life of Italian families. The lack of visibility of MIEM has reflected on the proposal to create a website as an alternative to disseminate the history of Italian immigration from the cultural assets available in the Museum. Therefore, the methodological methods used were bibliographic research on the culture of Italian immigration and the use of Information and Communication Technologies (ICT). The construction of MIEM website contributes to enhance the identity of the community, especially of the Italian immigrants descendants, besides being a way to preserve regional cultural heritage, as well as encouraging the dissemination of the Museum in order to attract tourists to an on-site visit and, consequently, regional development through tourism.